A SIMPLE METHOD FOR PREDICTION OF THE FLASH POINT OF MONOTERPENES - K., . Mokadem1,2; M., Mokadem1; K, Benzahi3; M, Korichi1; I, Benchikh6; M. L., . Belfar2 (university of eloued جامعة الوادي, 2020)
The flash point(Fp) is very important physical property used to estimate the risk of fire and fire hazard of a flammable to avoid the occurrence of fire or explosion, Monoterpenes are a class of terpenes, They have relevance to the pharmaceutical, cosmetic, agricultural, food industries and product principle of compounds volatile, and cause augment ignition the fire .In this papier, a group contribution and a group-interaction contribution approach are proposed to predict the flash point(Fp) of Monoterpenes compounds, A comprehensive database of 259 composes type monoterpenes, The best performance was observed for group-interaction contribution approach, with an average absolute relative deviation of 1.43% and a correlation coefficient of 0.906 Results also show that both models represent simple and reliable approaches for the estimation of the flash point(Fp).
Artical
Keywords: Monoterpenes; Group-interaction contribution approach; Goup contribution; Flash point(Fp); Prediction